Education planning in post-graduate education in Brazil - Horta, José Silvério Baía (2014)
A survey of information provided by post-graduate education programs for the 2000-2009 period, available at the Coordination for Training of Higher Education Personnel portal, reveals the progressive substitution of studies on educational planning by studies on assessment and management. This “emptying” of the 2000-2009 period is compared with the “fertility” of the 1970s and 1980s by analyzing the sources and content found in Master’s theses in education from PUC-Rio and the Getulio Vargas Foundation. In the conclusion, the article states that this “emptying” occurred simultaneously with the dismantling of the Brazilian planning system in the 1990s. It also suggests returning to the studies from the last National Educational Conferences and the difficulties in securing national congressional approval for the national educational plans proposed in them.